Productivity-Based Wages and Employment of People With Disabilities: International Usage and Policy Considerations. (December 2021) - Lysaght, Rosemary; Bobbette, Nicole; Ciampa, Maria Agostina
The legal requirement for employers to compensate workers at standard market wages, even if their work falls below competitive levels, is cited as a barrier to job entry for people with high support needs. Productivity-based wage systems have been implemented in some jurisdictions with a goal of addressing this challenge by providing an option for paying workers at rates commensurate with work output. This scoping review explored the international use of productivity-based wage systems, the theoretical and practical arguments that have been advanced for and against productivity-based wage systems, and the relative impact of such policies on employment outcomes. The review followed the procedures outlined by Arksey and O'Malley and included papers published from 2008 to 2017. The search identified 27 papers that were pertinent to at least one of the research questions. Only three countries emerged in the literature as having discernable productivity-based wage policies: Australia, Israel, and the United States. Limited evaluative evidence was identified on the impact of productivity-based wage systems on employment outcomes. There is, however, a robust debate evident concerning the socioeconomic, moral, and legal implications of this practice. Ongoing research is needed to inform policy on this contentious issue.